2020
DOI: 10.3389/fmed.2020.00103
|View full text |Cite
|
Sign up to set email alerts
|

What Predicts Different Kinds of Nonadherent Behavior in Elderly People With Parkinson's Disease?

Abstract: Background: Detailed knowledge about nonadherence to medication could improve medical care in elderly patients. We aimed to explore patterns and reasons for nonadherence in people with Parkinson's disease (PD) aged 60 years and older. Methods: Detailed clinical data and adherence (German Stendal Adherence with Medication Score) were assessed in 230 patients with PD (without dementia). Descriptive statistics were used to study reasons for nonadherence in detail, and general linear models were used to study asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 37 publications
3
23
1
4
Order By: Relevance
“…In line with earlier studies in PD, our multivariable analyses confirmed that depression, poor motor function (MDS-UPDRS III), lower education level, and higher LEDD are associated with nonadherence to medication (3,4,17). With reference to the study by Straka et al, we confirmed that the overall burden of NMS (NMSQ total score) is associated with nonadherence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with earlier studies in PD, our multivariable analyses confirmed that depression, poor motor function (MDS-UPDRS III), lower education level, and higher LEDD are associated with nonadherence to medication (3,4,17). With reference to the study by Straka et al, we confirmed that the overall burden of NMS (NMSQ total score) is associated with nonadherence.…”
Section: Discussionsupporting
confidence: 91%
“…Many reasons exist why people with PD do not or cannot follow instructions given for prescribed medical treatments. Several epidemiological and clinical factors were found to be associated with nonadherence to medication in PD, such as younger age, education level, marital status, depression and anxiety, poor cognition, longer disease duration, and regimen complexity (3,4,6,(10)(11)(12)(13)(14)(15)(16)(17). Recently, Straka et al studied the relationship between NMS and adherence in 124 subjects with PD recruited from movement disorder outpatient departments of university hospitals in Slovakia (18).…”
Section: Introductionmentioning
confidence: 99%
“…The low MoCA in our patients is due to the fact that some of the patients could not complete formal items of the MoCA, for example, because of visual or motor problems. In our previous study, we observed no association between self-reported adherence and cognition in people with PD [ 23 ].…”
Section: Discussionmentioning
confidence: 83%
“…Nonadherence to medication is a significant issue in PD. It results in frequent hospitalizations, reduced quality of life, and causes a financial burden for the health system [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. There are various reasons why people do not or cannot follow the given recommendations and instructions for the prescribed treatment.…”
Section: Field Of Activities and Responsibilitiesmentioning
confidence: 99%